2022
DOI: 10.3389/fimmu.2022.911922
|View full text |Cite
|
Sign up to set email alerts
|

SAPHO Syndrome Complicated by Ankylosing Spondylitis Successfully Treated With Tofacitinib: A Case Report

Abstract: Synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO) syndrome, a type of chronic inflammatory disease, is rare and difficult to treat. Osteoarthropathy with skin involvement is the primary clinical manifestation of SAPHO syndrome. The unknown pathogenesis of SAPHO syndrome is speculated to be related to individual genetic differences, immune levels, microorganisms, and environmental factors. Tofacitinib, a novel small-molecule Janus kinase (JAK) inhibitor, has been used to treat rheumatoid arthritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Specifically, this case was complicated with AS. To date, only a few cases of SAPHO syndrome with AS have been reported, and the case’s skin lesions and osteoarticular pain were significantly improved by tofacitinib or secukinumab when adalimumab was discontinued [ 24 , 25 ]. Some scholars believe that SAPHO syndrome can be classified in the category of SpA, which is between AS and PsA [ 3 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this case was complicated with AS. To date, only a few cases of SAPHO syndrome with AS have been reported, and the case’s skin lesions and osteoarticular pain were significantly improved by tofacitinib or secukinumab when adalimumab was discontinued [ 24 , 25 ]. Some scholars believe that SAPHO syndrome can be classified in the category of SpA, which is between AS and PsA [ 3 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also has a convinced effect in the treatment of psoriatic arthritis, 23 ankylosing spondylitis, 24 and SAPHO syndrome. 9,25,26 Although tofacitinib was reported to treat refractory cutaneous leukocytoclastic vasculitis, it had not been reported in HSP treatment. Based on the inference of the co-occurrence mechanism of the two diseases and our previous experiences, tofacitinib was prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that tofacitinib was effective in improving skin damage and reducing bone pain in a patient with ankylosing spondylitis combined with SAPHO syndrome. 5 In contrast, upadacitinib is a novel JAK1 inhibitor. Compared to the first-generation JAK inhibitor tofacitinib, upadacitinib can inhibit a single JAK protein with high selectivity without affecting other cytokines, thus potentially reducing adverse effects.…”
Section: O R R E S P O N D E N C E Novel Jak-1 Inhibitor Upadacitinib...mentioning
confidence: 99%